Depressive symptoms and C-reactive protein in a Brazilian urban community - Dressler, W. W.; Balieiro, M. C.; Ribeiro, R. P.; Dos Santos, J. E. (Assoc Bras Divulg Cientifica, 2006)
Psychological depression is an independent risk factor for coronary artery disease. C-reactive protein has been implicated as a mediator of the effect of psychological depression. Several studies have found that individuals, especially men, who report higher levels of psychological depression also have higher levels of C-reactive protein. The current study was undertaken to replicate these results in a Brazilian population, in which there is a much wider range of variation in both background characteristics (such as socioeconomic status) and coronary artery disease risk factors. A sample of 271 individuals was interviewed using the Center for Epidemiological Studies Depression Scale. Fasting blood samples were obtained and evaluated for C-reactive protein (assessed by a turbidimetric immunoassay using a Dade Behring kit) analysis in a subsample (N = 258) of individuals. The mean +/- SD C-reactive protein for the entire sample was 0.43 +/- 0.44, with 0.42 +/- 0.48 for men and 0.43 +/- 0.42 mg/ L for women. Data were analyzed using multiple regression analysis, controlling for age, sex, body mass index, socioeconomic status, tobacco use, and both total cholesterol and low-density lipoprotein cholesterol. Higher reported depressive symptoms were correlated with higher C-reactive protein for men (partial r = 0.298, P = 0.004) and with lower C-reactive protein for women (partial r = - 0.154, P = 0.059). The differences in the associations for men and women could be a result of differential effects of sex hormones on stress reactivity and immune response. On the other hand, this difference in the associations may be related to gender differences in the disclosure of emotion and the effect that self-disclosure has on physical health and immune response.
Keywords: C-reactive protein; depressive symptoms; Brazil; gender differences